Poverty and disease: the vicious circle - De La Cruz Vargas, Jhony Alberto (2018)
It is known that poverty and health is an interrelated phenomenon. The poorest countries have poor health indicators in relation to the countries with the highest incomes, and within each country the poorest people with health problems. This association reflects a causal relationship that works in both directions: poverty generates poor health, and poor health perpetuates poverty (vicious circle of poverty-disease) 1. However, it also means that people with problems of health do not have the same conditions as others, because these inequalities correspond to the limitations and opportunities different from each other and with others, and not with a tendency of sometimes different groups. DOI: 10.25176/RFMH.v18.n3.1585